2008
DOI: 10.1182/blood-2008-03-144261
|View full text |Cite
|
Sign up to set email alerts
|

Does Apo2L/TRAIL play any physiologic role in osteoclastogenesis?

Abstract: 10. Yee L, Fanale M, Dimick K, et al. A phase 1B safety and pharmacokinetic (PK) study of recombinant human Apo2L/TRAIL in combination with rituximab in patients with low-grade non-Hodgkin lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…38 Finally, Labrinidis et al found no direct effects of Apo2L/TRAIL on osteoclast differentiation and activity. 45 It is noteworthy that Labrinidis used clinical grade rhApo2L/TRAIL in their studies, which is in accordance with our studies. It has been established that different recombinant versions of Apo2L/TRAIL may yield a broad range of different biological activities and this could lead to a discrepancy in the results.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…38 Finally, Labrinidis et al found no direct effects of Apo2L/TRAIL on osteoclast differentiation and activity. 45 It is noteworthy that Labrinidis used clinical grade rhApo2L/TRAIL in their studies, which is in accordance with our studies. It has been established that different recombinant versions of Apo2L/TRAIL may yield a broad range of different biological activities and this could lead to a discrepancy in the results.…”
Section: Discussionsupporting
confidence: 79%
“…45,46 Our studies were not designed to directly address the role of rhApo2L/TRAIL on osteoclastogenesis, but rather the combined effects of RANK-Fc and rhApo2L/TRAIL on the growth of skeletal tumors. However, we did not see a significant effect of rhApo2L/TRAIL on serum TRAP5b levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our detailed histomorphometric and micro-CT analysis of the contralateral non-tumor-bearing bones of Apo2L/TRAIL-treated animals showed no significant effect of Apo2L/TRAIL on any bone morphometric parameter. In contrast, treatment with the antiresorptive bisphosphonate zoledronic acid, which was used for comparison as a positive control, resulted in a significant increase in bone mass as expected (39). Recently, we reported on the effect of Apo2L/TRAIL on osteoclast differentiation and bone resorption using three independent in vitro models of osteoclastogenesis (39).…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, treatment with the antiresorptive bisphosphonate zoledronic acid, which was used for comparison as a positive control, resulted in a significant increase in bone mass as expected (39). Recently, we reported on the effect of Apo2L/TRAIL on osteoclast differentiation and bone resorption using three independent in vitro models of osteoclastogenesis (39). We showed that Apo2L/TRAIL did not block RANKL-mediated osteoclast differentiation or bone resorption from human peripheral blood mononuclear cells or from the murine monocytic cell line, RAW264.7.…”
Section: Discussionmentioning
confidence: 64%
“…Apo2L/ TRAIL binds to OPG, although with a lower affinity, and this has been proposed to regulate differentiation and survival of mature osteoclasts (Zauli et al, 2004(Zauli et al, , 2008Vitovski et al, 2007). However, considering that Apo2L/TRAIL-knockout mice are viable and develop normal bone density (Cretney et al, 2002;NewsomDavis et al, 2009), it remains unclear whether this ligand has a significant physiological role in regulating osteoclastogenesis (Labrinidis et al, 2008).…”
Section: Drsmentioning
confidence: 99%